Penerapan Algoritma Gronsfeld Dengan Pembangkit Kunci Quicksort Untuk Mengamankan Pesan Rahasia - Ria Ramadhani Syahputri; Mesran Mesran; Murdani Murdani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The numerous issues often encountered in securing confidential messages revolve around message leaks. Message leaks occur through various means, such as eavesdropping. Eavesdropping happens when unauthorized parties manage to access and obtain information from ongoing communications. One way to maintain the confidentiality of secret messages is through encryption and decryption, known as cryptography, achieved by transforming the original message (plaintext) into a secret message (ciphertext). In this study, the results of the encrypted character ciphertext are v, v, w, ^, ™, ʽ, ¦, ¥, -, ¼, Ý, ó, ⁒, x, [],